Histopathological features of relapse cases in leprosy - Kaur, Navdeep (International Journal of Research in Medical Sciences, 2020)
Leprosy is unique in terms of the nature of the causative organism (Mycobacterium leprae), the chronicity of the disease, its prolonged treatment and the definitions of “cure” and “relapse.” The principal mode of assessing the efficacy of therapeutic regimens in leprosy is the “relapse rate.” There are wide variations in estimates of relapse rates after the World Health Organization (WHO) multidrug therapy in different regions. The important predisposing factors for relapse include the presence of “persister” bacilli, monotherapy, inadequate/irregular therapy, presence of multiple skin lesions/thickened nerves and lepromin negativity. The conventional methods of confirming activity or relapse in an infectious disease (demonstration and/or culture of the etiologic agent) have limited utility in leprosy because of the difficulty in demonstrating bacilli in paucibacillary (PB) cases and absence of a method of in vitro cultivation of M. leprae. Bacteriological parameters are useful in multibacillary (MB) leprosy, whereas in PB leprosy, the criteria for relapse depend primarily on clinical features. Although there are no widely available serologic tests for leprosy other than in a research setting, various immunological tests may be useful for monitoring patients on chemotherapy as well as for confirming suspected cases of relapse. The main differential diagnoses for relapse are reversal reactions, erythema nodosum leprosum and reactivation/resistance/reinfection. The most reliable criteria for making an accurate diagnosis of relapse include clinical, bacteriological and therapeutic criteria. Additional ones that may be used, depending on the setting, are histopathological and serologic criteria.